Psychogenic polydipsia in a female adolescent without a psychiatric background: A case report. Issue 4 (27th February 2021) - Nauwynck, Elise; Van De Maele, Karolien; Vanbesien, Jesse; Staels, Willem; De Schepper, Jean; Gies, Inge
Abstract: Psychological stress is a risk factor for primary polydipsia in adolescents without psychiatric comorbidity. Taking a detailed family and social history can help to distinguish primary polydipsia from diabetes insipidus in adolescents with challenging presentations of polydipsia and polyuria. Abstract : Psychological stress is a risk factor for primary polydipsia in adolescents without psychiatric comorbidity. Taking a detailed family and social history can help to distinguish primary polydipsia from diabetes insipidus in adolescents with challenging presentations of polydipsia and polyuria.